Research on Comprehensive Evaluation of Low Carbon Economy Development Level Based on AHP-Entropy Method: A Case Study of Dalian. (December 2016) - Duan, Ye; Mu, Hailin; Li, Nan; Li, Linlin; Xue, Zhaoquan
Abstract: Based on the AHP-Entropy method, the evaluation system of the low carbon economy development level on Dalian is built. The comprehensive evaluation index of low carbon economy development level on Dalian is calculated from 2005 to 2014. The results show that the index reached the maximum in 2014 (0.6134), which indicates that low carbon construction on Dalian has obtained certain achievements, but to prevent a recurrence, the government should alert that the index may initially decrease, but will increase after it reaches a minimum.